Comparing Rapid and Specific Detection of Brucella in Clinical Samples by PCR-ELISA and Multiplex-PCR Method - Sharareh Mohammad Hasani; Reza Mirnejad; Vahhab Piranfar; Jafar Amani; Mohamad javad Vafadar (Iranian Society of Pathology, 2016)
Background: Rapid diagnosis and differentiation of Brucella is of high importance due to the side effects of antibiotics for the treatment of brucellosis. This study aimed to identify and compare PCR-ELISA as a more accurate diagnositc test with other common molecular and serological tests. Methods: In this experimental and sectional study, during March 2014 to Sep 2015, 52 blood samples of suspected patients with clinical symptoms of brucellosis were evaluated in medical centers all over Iran with serum titers higher than 1:80. Using two pairs of specific primers of Brucella abortus, B. melitensis and DIG-dUTP, Fragment IS711 (The common gene fragment in B. melitensis and B. abortus) was amplified. DIG-ELISA was performed using specific probes of these 2 species of Brucella and patterns were subsequently analyzed, then positive responses were compared by detecting gel electrophoresis. Results: PCR-ELISA method detected all 28 samples from 52 positive samples. Its sensitivity was 6.0 pg concentration of genomic DNA of Brucella. In gel electrophoresis method, 22 samples of all positive samples were detected. PCR-ELISA was more efficient than PCR and bacterial culture method at P-value Conclusion: PCR-ELISA molecular method is more sensitive than other molecular methods, lack of mutagenic color and also a semi-quantitative ability. This method is more effective and more accurate compared to PCR, serology and culture of bacteria. PCR-ELISA does not have false responses. The limitation of this method is detection of bacteria in the genus compared to Multiplex PCR and Gel Electrophoresis.